2002
DOI: 10.1093/ptj/82.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Is Base of Support Greater in Unsteady Gait?

Abstract: Gait at preferred speed permitted the unsteady subjects and the comparison subjects to select similar IFD values, but at the cost of slower gait in the unsteady subjects. When required to walk at a "normal" pace of 120 steps/min, subjects with vestibulopathy increased their IFD. These data suggest that wide-based gait alone cannot differentiate between subjects with and without balance impairments. Base of support and other whole-body kinematic variables are mechanical compensations of vestibulopathic instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 24 publications
4
43
0
Order By: Relevance
“…5 When subjects with vestibular disorders walked at their self-selected speed, their stance width was similar to that of control subjects but at the expense of decreased speed. 6 Increased stance width was noted when these same subjects were asked to walk at an externally paced speed (120 steps per minute). 6 People with vestibular disorders ambulate with increased stance time variability, 7 decreased gait speed, 6,8,9 and increased stride time variability.…”
mentioning
confidence: 95%
“…5 When subjects with vestibular disorders walked at their self-selected speed, their stance width was similar to that of control subjects but at the expense of decreased speed. 6 Increased stance width was noted when these same subjects were asked to walk at an externally paced speed (120 steps per minute). 6 People with vestibular disorders ambulate with increased stance time variability, 7 decreased gait speed, 6,8,9 and increased stride time variability.…”
mentioning
confidence: 95%
“…The pattern has exaggerated knee flexion, increased hip adduction and internal rotation (Cherng et al, 2007). Therefore in the present study, an increase of base of support may be caused by reduced hip adduction pattern with supporting foot and ankle (Krebs at al, 2002). Also the stance time shortened along with increased velocity or stability (Kirtley et al, 1985).…”
Section: Discussionmentioning
confidence: 51%
“…Some investigators have administered paced walking, where either walking speed is controlled as on a treadmill, 58 or cadence is standardized by a metronome. 59 This practice may, however, affect walking behaviour and, therefore, restrict the validity of results and so it is preferred by different investigators to have the subjects walking at a self-preferred speed without external control. 60 Additionally, it has been shown that there are gender differences in the biomechanical properties of the lower extremities.…”
Section: Discussionmentioning
confidence: 99%